“Listening Out” to Experimental Music in Canada: Publics, Subjects, Places - Strachan, Jeremy (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2016)
In 2016 Michael Snow and Mani Mazinani improvised on vintage analog synthesizers in Yonge-Dundas Square, filling Toronto’s busiest commercial commons with retro-futuristic sonic filigree; almost fifty years earlier, Otto Joachim’s four-channel electronic sound installation Katimavik furnished the Canadian Pavilion at Expo 67 in Montreal with uncannily similar sounds. In both cases, listeners perambulated amongst a sonic-spatial architecture defined by publicness and auditory plurality. In the intervening decades, non-profit artist-run centres proliferated across the country, offering refuge for local experimentalists to develop their craft in the name of regional and national cultural growth. Such is experimental music’s longstanding position on the margins and centres of listening in Canada: its history as a niche practice is replete with attempts to insert itself into the everyday. I argue that the diffusion of experimental music into increasingly quotidian spheres in Canada offers a way to understand how place is engendered through the intersubjectivity of listening—an act implicated in a range of agentive processes. Different from other listening contexts, in listening to experimental music we become interpellated into a relational nexus where the loci of composition, performance, and perception become distributive and unstable. I thus suggest that listening to experimental music in Canada can be thought of as a “listening out” an “attentive and anticipatory communicative disposition.” The examples serve as case studies for refiguring the engagement between creative music and the commons in Canada—what experimental music can “mean in the world.”